Structure of the periplasmic copper‐binding protein CueP from Salmonella enterica serovar Typhimurium. Corrigendum. (1st July 2014) - Yoon, Bo‐Young; Kim, Yong‐Hak; Kim, Nahee; Yun, Bo‐Young; Kim, Jin‐Sik; Lee, Joon‐Hee; Cho, Hyun‐Soo; Lee, Kangseok; Ha, Nam‐Chul
<x xml:space="preserve">Abstract</x> The affiliation of two of the authors of Yoon et al. [(2013). D69, 1867–1875] is corrected.